2007
DOI: 10.1177/1466424007079494
|View full text |Cite
|
Sign up to set email alerts
|

Review: Psychological responses to injury in competitive sport: a critical review

Abstract: Research has attempted to examine the psychological impact of athletic injury to assist rehabilitation personnel when treating injured athletes. Sports trainers, sports therapists, physiotherapists, medical staff and sports psychologists should be aware of psychological factors impacting on the injury experience when involved in an athlete's rehabilitation. A number of models have been proposed as useful frameworks for investigating and describing the psychological response to athletic injury. Many researchers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 25 publications
2
64
0
Order By: Relevance
“…In general, findings from the current study add support to the integrated model of psychological response to sport injury [3] and to other previous research findings that athletes incurring sport injuries experience not only the physical consequences of an injury, but also the psychosocial responses surrounding the sport injury [12,[21][22][23]. Findings from the current study provide evidence for a need to study the role of injury type to better understand the psychosocial responses across the time course of the injury process [3].…”
Section: Injury Storysupporting
confidence: 61%
“…In general, findings from the current study add support to the integrated model of psychological response to sport injury [3] and to other previous research findings that athletes incurring sport injuries experience not only the physical consequences of an injury, but also the psychosocial responses surrounding the sport injury [12,[21][22][23]. Findings from the current study provide evidence for a need to study the role of injury type to better understand the psychosocial responses across the time course of the injury process [3].…”
Section: Injury Storysupporting
confidence: 61%
“…Although previous research has revealed a number of positive outcomes of sport injury, 6,7,13 it has not indicated that the experience of injury can be therapeutic in and of itself. 15 However, the present findings suggest that for some of these athletes, the acceptance of a higher meaning to their injury experience may have been therapeutic.…”
Section: DI Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 81%
“…The present study represented an attempt to extend the work of Walker et al 14,15 by further exploring the possible meaning athletes derive from their injury experience. To accomplish this task we employed an interview technique based on the philosophical tenets of phenomenology.…”
mentioning
confidence: 94%
“…Clear evidence in the literature 78,79 indicates that an injured athlete's emotional responses can affect subsequent behavior and self-regulatory capacity during rehabilitation. For example, feelings of self-doubt may limit the motivation or self-regulation needed to engage in rehabilitation activities as planned.…”
Section: Sport Medicine Professional As the Primary Treatment Providermentioning
confidence: 99%